Perbandingan Hasil Belajar Biologi antara Kelas yang Menerapkan Pembelajaran Inkuiri Terbimbing dengan Menggunakan Handout dan Kelas yang Menerapkan Pembelajaran Inkuiri Bebas Menggunakan Handout pada Siswa Kelas VII MTs Al-Muttaqin Pekanbaru Tahun Ajaran 2013/2014 - Hasniyati, Hasniyati; Elfis, Elfis; Hidayati, Nurkhairo (Multiverse: Open Multidisciplinary Journal, 2023)
This study aimed to compare learning outcomes in the implementation of biology guided inquiry learning using handouts versus inquiry learning with free handouts in Class VII at MTs Al - Muttaqin Pekanbaru during the Academic Year 2013/2014, focusing on the ecosystem. Data collection spanned from March to April 2014. The experimental groups included VIIB (X1) utilizing guided inquiry with handouts and VIIa (X2) employing inquiry learning with free handouts. The mean KDP scores for X1 (VIIB) and X2 (VIIa) were 86.26 and 79.99, respectively. The average KI scores were 83.03 for X1 (VIIB) and 72.62 for X2 (VIIa). T-test results, with KDP t-value of 2.23 (table = 2.00) and KI t-value of 3.10 (table = 2.00) at a 5% significance level, indicate significant differences in learning outcomes. In conclusion, disparities exist in learning outcomes between classes implementing guided inquiry with handouts and those employing free inquiry learning with handouts at MTs Al - Muttaqin Pekanbaru during the specified academic year.